Impact of error analysis on the composition the outer crust of a neutron star. (December 2020) - Neill, D; Medler, K; Pastore, A; Barton, C
Abstract: By means of bootstrap technique, we perform a full error analysis on the Duflo-Zucker mass model. We illustrate the impact of such study on the predicted chemical composition of the outer crust of a non-accreting neutron star. We define an existence probability for each nuclear species as a function of the depth of the crust. We observe that, due to statistical uncertainties, instead of having a well defined transition between two successive layers, we have a mixture of two species.